Neutrosophic k-Ideal in Q-algebra - Taeh Shadhan , Mortda; Laith Abd Algalib , Shahad (Pure Sciences International Journal of Kerbala, 2026)
In this paper, the k-ideals in Q-algebras are studied in the framework of single-valued neutrosophic sets. After recalling some basic notions related to Q-algebras and single-valued neutrosophic sets, the concept of single-valued neutrosophic k-ideals are introduced. Several properties and characterizations of single-valued neutrosophic k-ideals are investigated. Moreover, the relationships between single-valued neutrosophic k-ideals and single-valued neutrosophic ideals are discussed. Illustrative examples are provided to support the theoretical results.